Modeling and Thermodynamic Analysis of Solar Collector Cogeneration for Residential Building Energy Supply - Ghassan F. Smaisim; Azher M. Abed; Salema K. Hadrawi; Ali Shamel (Journal of Engineering)
Concerns about limited energy resources and environmental problems are growing. One of the solutions to increase energy efficiency is to produce it sparsely. In this regard, cogeneration systems are of particular importance. The home sector is one of the most consumed sectors due to the potential of solar radiation in this country, a system of simultaneous generation of electricity and heat for the home sector has been proposed, and modeling operations have been performed on the proposed system. The results show that the proposed system is capable of supplying more than 85% of hot water demand and annual production of 316.36 kWh of electricity.